2019
DOI: 10.2147/dmso.s207087
|View full text |Cite
|
Sign up to set email alerts
|

<p>Self-reported oral health and quality of life in patients with type 2 diabetes mellitus in primary care: a multi-center cross-sectional study</p>

Abstract: Background: Guidelines for primary diabetes care recommend to pay attention to oral health in patients with diabetes mellitus type 2 (T2DM). However, research about dental care utilization and the extent of problems regarding oral health in these patients is limited. Purpose: To assess self-reported oral health, general health-related quality of life (QoL) and oral health-related QoL in patients with T2DM who regularly attend a family physician office. Methods: Family physician offices were recruited in the ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
21
3
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 52 publications
6
21
3
7
Order By: Relevance
“…In our study, half of the respondents reported to have other chronic diseases in additional to diabetes and the majority had a lower socio-economic status, so these factors would have played an additional role in the higher prevalence of poor oral health status. More than half of the patients reported having one or more oral health problems with dry mouth being the most prevalent issue and this was similar to the findings of a study from Netherlands [ 27 ]. However, the mean (SD) OHIP-14 severity score (11.38 ± 12.0) found in our study was significantly higher compared to that reported among participants in the Dutch study (2.5 ± 5.2) [ 27 ].…”
Section: Discussionsupporting
confidence: 87%
“…In our study, half of the respondents reported to have other chronic diseases in additional to diabetes and the majority had a lower socio-economic status, so these factors would have played an additional role in the higher prevalence of poor oral health status. More than half of the patients reported having one or more oral health problems with dry mouth being the most prevalent issue and this was similar to the findings of a study from Netherlands [ 27 ]. However, the mean (SD) OHIP-14 severity score (11.38 ± 12.0) found in our study was significantly higher compared to that reported among participants in the Dutch study (2.5 ± 5.2) [ 27 ].…”
Section: Discussionsupporting
confidence: 87%
“…Regarding CCs, the prevalence of OHSU in the previous 6 months was 24.3% in participants with diabetes. Although this was greater than the overall percentage of participants who received OHSU (18.5%) in our study, some studies of patients with diabetes have reported even higher prevalence rates of OHSU (between 40% and 73%) [ 27 - 29 ]. However, those studies evaluated dental visits during the previous 12 months, unlike our approach, which involved a 6-month interval.…”
Section: Discussioncontrasting
confidence: 73%
“…Even when this performance was greater than the overall percentage of OHSU (18.5%) in our study, some studies on diabetic patients have reported a higher prevalence of OHSU (between 40% and 73%) [27][28][29]. However, these studies evaluated dental visits taking into account the last 12 months, contrary to our approach involving a 6-month interval.…”
Section: Discussioncontrasting
confidence: 72%
“…Both children/adolescents [12] and adults with pre-diabetes or type 2 diabetes, respectively, visit the dentist less frequently than their normoglycemic peers [119]. For example, nearly one-quarter of Dutch patients attending family physicians' offices did not have regular dental visits [113]. Fig.…”
Section: Oral Health Care and Awarenessmentioning
confidence: 99%
“…Furthermore, even though periodontitis is regarded a ''silent" disease due to its potential lack of noticeable signs and symptoms during the majority of its development, up until movement or loosening of the tooth, a systematic review limited to clinically assessed (not self-reported) periodontitis demonstrated the important role of periodontitis in the oral health impact on quality of life [112]. In a study in Amsterdam of 764 patients with type 2 attending 24 general medical offices, both oral health and general health related quality of life were diminished [113].…”
mentioning
confidence: 99%